Coal Flotation in Saline Water: Effects of Electrolytes on Interfaces and Industrial Practice. (2nd January 2021) - Bournival, Ghislain; Zhang, Feng; Ata, Seher
ABSTRACT: Coal preparation plants are increasingly turning to alternative sources of water to reduce their consumption of fresh water. These alternative sources can vary significantly in ionic content. This review discusses the effect of dissolved inorganic electrolytes on coal flotation. It is argued that increasing process monitoring will enable a better understanding of the effects of salts on the flotation process. A pragmatic approach in monitoring is essential to differentiate significant factors from insignificant ones controlling the performance of coal flotation units in salt water. The effects of inorganic electrolytes on the air–water interface and the solid–liquid interface are reviewed to assist in the interpretation of industrial results.